Os conceitos de eletricidade vítrea e eletricidade resinosa segundo Du Fay - Boss, Sérgio Luiz Bragatto [UNESP]; Caluzi, João José [UNESP] (My University, 2007)
In the 1730 decade, Charles François De Cisternay Du Fay enunciated two general principles that, according to him, ruled the electric phenomena. The goal of this paper is to discuss Du Fay's proposal and its later interpretation. We have organized the paper in three parts. In the first one, we will present a short biography of Du Fay. Next, we discuss his proposal for vitreous electricity and resinous electricity. Finally, we present the translation of letter of Du Fay to the Duke of Richmond in which he describes his discoveries on electricity. Copyright by the Sociedade Brasileira de Física.
Concepts of vitreous electricity and resinous electricity according Du Fay
Keywords: Du Fay; Resinous electricity; Vitreous electricity